تطبيقات قاعدة الحكم يدور مع علته وجودًا وعدمًا: المعاملات المالية أنموذجًا - Muhammad Said Almujahed; Mohammad Said Titoon Alrashdi (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2022)
The research is significant because it examines the jurisprudential applications of the maxim